1997
DOI: 10.4319/lo.1997.42.5.0856
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 32Si as a tracer for measuring silica production rates in marine waters

Abstract: The radioisotope 32Si was evaluated as a tracer for measuring silica production rates in marine waters. j2Si is a weak p-emitter that decays to 32P allowing the isotope to be used to determine simultaneously the production rate of biogenic silica and organic phosphorus. High specific activity '*Si, 42,000-52,000 Bq (pug Si)-I, was produced by the proton spallation of KCl. Reasonable tracer additions result in only nanomolar increases in the ambient silicic acid and orthophosphate concentrations during producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 18 publications
3
47
0
Order By: Relevance
“…Laboratory studies indicate a reduction of biogenic silica content with increasing pCO 2 levels (Milligan et al 2004;Hoppe et al 2015). To our knowledge, our study is the first to apply the 32 Si uptake technique (Brzezinski and Phillips, 1997) to assess pCO 2 effects on natural phytoplankton assemblages. Our results showed that OA had no effect on either Si uptake (Table 2) or bSi:C ratios (Table 3).…”
Section: Assemblages Did Not Respond To Ocean Acidificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory studies indicate a reduction of biogenic silica content with increasing pCO 2 levels (Milligan et al 2004;Hoppe et al 2015). To our knowledge, our study is the first to apply the 32 Si uptake technique (Brzezinski and Phillips, 1997) to assess pCO 2 effects on natural phytoplankton assemblages. Our results showed that OA had no effect on either Si uptake (Table 2) or bSi:C ratios (Table 3).…”
Section: Assemblages Did Not Respond To Ocean Acidificationmentioning
confidence: 99%
“…The activity of 32 Si in the samples was determined by gas-flow proportional counting at secular equilibrium using a Risø 25-5 low-level beta GM multicounter (Krause et al 2011). Biogenic silica production rates (lmol Si L -1 d -1 ) were calculated as in Brzezinski and Phillips (1997).…”
Section: Primary Production and Si Uptake Assaysmentioning
confidence: 99%
“…NO 3 -uptake rates were calculated using equations in Dugdale & Goering (1967). These values compared well with NO 3 -uptake rates calculated using equations adapted from Brzezinski & Phillips (1997).…”
Section: Methodsmentioning
confidence: 99%
“…After incubation, samples were vacuum-filtered (<150 mm Hg) onto 0.6 µm polycarbonate filters and allowed to air dry ( 32 Si) or filtered onto pre-combusted Whatman GF/F glass fiber filters (~0.7 mm) and stored frozen in pre-combusted aluminum foil packets ( 15 N). Samples with 32 Si were stored until 32 Si and 32 P reached secular equilibrium (> 3 mo) and 32 Si activity was assayed according to Brzezinski & Phillips (1997). Si(OH) 4 uptake rates were calculated as described therein.…”
Section: Methodsmentioning
confidence: 99%
“…Krause et al (2008) measured bSiO 2 silica production rates during this study using the 32 Si tracer and incubation method described by Brzezinski and Phillips (1997) and Brzezinski et al (2001). Depth integrated (0 -140 m) bSiO 2 production rates averaged 1.03 ± 0.96 (n = 17) and 2.28 ± 2.06 (n = 9) mmol Si m -2 d -1 for the West and East Transects, respectively, a substantial increase over previous Sargasso Sea measurements (Brzezinski and Kosman, 1996;Brzezinski and Nelson, 1995;Nelson and Brzezinski, 1997).…”
Section: Bsio 2 Exportmentioning
confidence: 99%